Alergia y Covid-19 - Isler I, Dayanne; Guzmán M, Mª Antonieta (Revista Hospital Clínico Universidad de Chile, 2021)
Atopic diseases, especially asthma may confer increased susceptibility to viral infections, however, such patients have been largely unaffected in the current Covid-19 pandemic. This favorable course could be explained by a protective role of cytokines and cells involved in an immune response with a T2 profile. In spite of the favorable course observed, it is a priority to maintain with its basic treatments to ensure a good control of the pathology. With respect the immunization process being carried out in patients with a history of allergic reactions in different degrees, the recommendation of the type of vaccine and the protocol for its administration should be individualized according to a risk stratification prior to its administration.